A Mendelian randomization investigation of the causal association between the gut microbiota and sleep disorders - Yan, Wei; Zhuang, Zhenzhen; Gao, Yuhao; Wang, Yuntao; He, Daikun (Frontiers in Microbiology, 2024)
Background: Increasing numbers of people are suffering from sleep disorders. The gut microbiota of these individuals differs significantly. However, no reports are available on the causal associations between specific gut microbiota and sleep disorders.Methods: Data on gut genera were obtained from the MiBioGen consortium.Twenty-four cohorts with 18,340 individuals of European origin were included. Sleep disorder data, which included 216,454 European individuals, were retrieved from the FinnGen Biobank.Subsequently,two-sample Mendelian randomization was performed to analyze associations between sleep disorders and specific components of the gut microbiota.Coprobacter and sleep disorders (OR = 0.797, 95% CI = 0.66-0.96, and P = 0.016), a positive correlation between Lachnospiraceae and sleep disorders (OR = 1.429, 95% CI = 1.03-1.98, and P = 0.032), a negative association between Oscillospira and sleep disorders (OR = 0.745, 95% CI = 0.56-0.98, and P = 0.038), and a negative association between Peptococcus and sleep disorders (OR = 0.858, 95% CI = 0.74-0.99, P = 0.039).A significant causal relationship was found between four specific gut microbiota and sleep disorders. One family, Lachnospiraceae, was observed to increase the risk of sleep disorders, while three genera, namely, Coprobacter, Oscillospira, and Peptococcus, could reduce the risk of sleep disorders. However, further investigations are needed to confirm the specific mechanisms by which the gut microbiota affects sleep.